Relationship Between Respondent Characteristics and The Level of Knowledge of Outpatient Patients' Family About Radiation Signs in The Radiology Installation of Pasaman Barat Regional Hospital - Yori Rahmadianti; Samsa Putri; Sagita Yudha (PT. Hafasy Dwi Nawasena, 2026)
Signs that have been installed in the Radiology Installation of West Pasaman Hospital are indicator lights, red triangle radiation hazard signs, and radiation hazard signs for pregnant women. This study aims to determine the relationship between the characteristics of respondents, namely age, gender and education with the level of knowledge of families of outpatients.The type of research used in this study is quantitative. This research was conducted at the radiology installation of West Pasaman Hospital. The population of this study were families of outpatients at the radiology installation of Pasaman Barat Hospital. The sample in this study amounted to 82 people with purposive sampling technique. Data collection used a questionnaire, and the data obtained was then processed using the SPSS application. The results showed that in this study there were three characteristics of respondents, namely age with p value <0.05, which means Ho is rejected and Ha is accepted, so there is a significant relationship, gender with p value <0.05, and gender with p value <0.05.